Doxorubicin loaded dual pH- and thermo-responsive magnetic nanocarrier for combined magnetic hyperthermia and targeted controlled drug delivery applications. Issue 24 (19th February 2016) - Hervault, Aziliz; Dunn, Alexander E.; Lim, May; Boyer, Cyrille; Mott, Derrick; Maenosono, Shinya; Thanh, Nguyen T. K.
Abstract : Dual pH- and thermo-responsive magnetic nanocomposite as a platform for hyperthermia and controlled drug delivery in cancer treatment. Abstract : Magnetic nanocarriers have attracted increasing attention for multimodal cancer therapy due to the possibility to deliver heat and drugs locally. The present study reports the development of magnetic nanocomposites (MNCs) made of an iron oxide core and a pH- and thermo-responsive polymer shell, that can be used as both hyperthermic agent and drug carrier. The conjugation of anticancer drug doxorubicin (DOX) to the pH- and thermo-responsive MNCs via acid-cleavable imine linker provides advanced features for the targeted delivery of DOX molecules via the combination of magnetic targeting, and dual pH- and thermo-responsive behaviour which offers spatial and temporal control over the release of DOX. The iron oxide cores exhibit a superparamagnetic behaviour with a saturation magnetization around 70 emu g −1 . The MNCs contained 8.1 wt% of polymer and exhibit good heating properties in an alternating magnetic field. The drug release experiments confirmed that only a small amount of DOX was released at room temperature and physiological pH, while the highest drug release of 85.2% was obtained after 48 h at acidic tumour pH under hyperthermia conditions (50 °C). The drug release kinetic followed Korsmeyer–Peppas model and displayed Fickian diffusion mechanism. From the results obtained it can be concluded that this smart magnetic nanocarrier is promising for applications in multi-modal cancer therapy, to target and efficiently deliver heat and drug specifically to the tumour.